2008
DOI: 10.1038/ncponc1183
|View full text |Cite
|
Sign up to set email alerts
|

CTLA-4 blockade with ipilimumab induces significant clinical benefit in a female with melanoma metastases to the CNS

Abstract: The patient was treated with ipilimumab on a compassionate-use program and dexamethasone, celecoxib, and levetiracetam to treat the symptoms and seizures. Postoperative stereotactic radiosurgery was initiated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
102
2
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(111 citation statements)
references
References 14 publications
2
102
2
5
Order By: Relevance
“…Ni la vaccination, ni la dacarbazine ne semblent apporter un bénéfice supplémentaire. D'autre part, quelques résultats obtenus sur de petits effectifs de patients suggèrent une efficacité possible sur les métastases cérébrales de mélanome qui sont habituellement réfractaires à tout traitement [22,29,30].…”
Section: L'expérience De L'ipilimumabunclassified
“…Ni la vaccination, ni la dacarbazine ne semblent apporter un bénéfice supplémentaire. D'autre part, quelques résultats obtenus sur de petits effectifs de patients suggèrent une efficacité possible sur les métastases cérébrales de mélanome qui sont habituellement réfractaires à tout traitement [22,29,30].…”
Section: L'expérience De L'ipilimumabunclassified
“…First, the optimal timing of SRS and ipilimumab is unknown. Furthermore, given the possibility of pseudoprogression from both radiosurgery 68,69 and ipilimumab, 70 care must be taken when determining progression on surveillance imaging after the combination of SRS and ipilimumab.…”
Section: Ctla-4 Inhibition and Intracranial Radiosurgerymentioning
confidence: 99%
“…Up to date, no single treatment modality has been systematically tested in a randomized clinical trial to demonstrate an impact on disease-specific survival. Encouragingly, treatment with CTLA-4 mAb has resulted in durable control of brain metastases (Hodi et al 2008b;Margolin et al 2010;Schartz et al 2010). While the phase III trials with ipilimumab excluded patients with prior or current brain metastasis, a parallel expanded access trial of ipilimumab enrolled patients who were later found to have small brain metastases that had not been treated with radiation.…”
Section: Introductionmentioning
confidence: 99%